Study of Changes for Total Sialic Acid and Lipid-Bound Sialic Acid Levels in Tuberculosis and Lung cancer - Rissan, Wesam (University of Thi-Qar Journal of Science, 2019)
Sialic acid (SA) have been used as one of laboratory markers in diagnosis a variety of pathological conditions, and it have been found to be elevated in a number of different cancers .Many studies have shown that mean values of total sialic acid (TSA) or lipid-bound sialic acid (LSA) were higher in patients with cancer than in normal subjects .The aim of the present study was to determine the serum of total sialic acid (TSA), lipid-bound sialic acid (LSA),total protein (TP) and TSA/TP levels in the(Tuberculosis TB and Lung cancer LC ) compared with healthy controls , data analysis indicated a significant increase ( P=0.0001 ) in TSA and LSA levels in (TB,LC) groups in comparison with healthy controls, no difference was observed in TSA concentrations between (TB,LC) groups, no difference LSA levels were observed when (TB) patients compared with healthy controls ,.The concentration of TP was slightly elevated( P=0.042 ) in (TB,LC) groups comparison with healthy controls ,there was a significant increased ( P=0.0001 ) in TSA/TP levels in (TB,LC) groups in comparison with healthy controls.